KDIGO clinical practice guideline for the care of kidney transplant recipients: a summary - Kasiske, Bertram L.; Zeier, Martin; Chapman, Jeremy R.; Craig, Jonathan C.; Ekberg, Henrik; Garvey, Catherine A.; Green, Michael D.; Jha, Vivekanand; Josephson, Michelle A.; Kiberd, Bryce A.; Kreis, Henri A.; McDonald, Ruth A.; et al. (Kidney international, 2009)
The 2009 Kidney Disease: Improving Global Outcomes (KDIGO) clinical practice guideline on the monitoring, management, and treatment of kidney transplant recipients is intended to assist the practitioner caring for adults and children after kidney transplantation. The guideline development process followed an evidence-based approach, and management recommendations are based on systematic reviews of relevant treatment trials. Critical appraisal of the quality of the evidence and the strength of recommendations followed the Grades of Recommendation Assessment, Development, and Evaluation (GRADE) approach. The guideline makes recommendations for immunosuppression and graft monitoring, as well as prevention and treatment of infection, cardiovascular disease, malignancy, and other complications that are common in kidney transplant recipients, including hematological and bone disorders. Limitations of the evidence, especially the lack of definitive clinical outcome trials, are discussed and suggestions are provided for future research. This summary includes a brief description of methodology and the complete guideline recommendations but does not include the rationale and references for each recommendation, which are published elsewhere.